2017
DOI: 10.1016/j.pmrj.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Dependent Effects of AbobotulinumtoxinA (Dysport) on Spasticity and Active Movements in Adults With Upper Limb Spasticity: Secondary Analysis of a Phase 3 Study

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It is well known that the amount of active BoNT-A injected is positively correlated to the duration of action (muscle paralysis) of the treatment. This dose–duration relationship has been clearly demonstrated in animal models [28], and a dose–efficacy relationship has been seen in patients with upper limb spasticity, though duration of response was not explored in this study [40]. Other clinical studies from the field of aesthetic medicine, however, have provided evidence for a dose–duration relationship [41,42,43].…”
Section: Discussionmentioning
confidence: 62%
“…It is well known that the amount of active BoNT-A injected is positively correlated to the duration of action (muscle paralysis) of the treatment. This dose–duration relationship has been clearly demonstrated in animal models [28], and a dose–efficacy relationship has been seen in patients with upper limb spasticity, though duration of response was not explored in this study [40]. Other clinical studies from the field of aesthetic medicine, however, have provided evidence for a dose–duration relationship [41,42,43].…”
Section: Discussionmentioning
confidence: 62%
“…[10][11][12] Full details of patient flow and of patient demographics, baseline characteristics, and mean dose of abobotulinumtoxinA injected into each of the muscle groups can be found in the original study publications. [10][11][12]18 In general, patient demographics and baseline characteristics were similar between studies; across double-blind treatment groups of both studies, the mean age was 51 to 53 years, 62% to 70% of patients were male, and in 83% to 92% of patients, the cause of spastic paresis was stroke. CX A values at baseline of the double-blind study are shown in Table 1.…”
Section: Patientsmentioning
confidence: 88%
“…Four such studies have demonstrated the efficacy of aboBoNTA (Dysport®) in improving clinical outcomes and function across a number of indications; these include adults with upper or lower limb spastic paresis following a stroke or traumatic brain injury ( 15 17 ), children with lower limb spastic paresis as a result of cerebral palsy ( 18 , 19 ), and adults with cervical dystonia ( 20 ). These trials established the clinical efficacy of aboBoNTA; a separate dose-ranging analysis in the upper limb reported dose-dependent improvements in spasticity and in active movement with aboBoNTA ( 21 ).…”
Section: Introductionmentioning
confidence: 99%